Design of Monitoring System for Hazardous Gas and Fire Detection In Building Based On Internet of Things - Zaini Zaini; Taffany Hudalil Alvy (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Fires and gas leaks are events that still occur frequently. This incident is usually caused by various factors including leakage of LPG gas cylinders, cigarette butts that are disposed of carelessly, short circuits of electric current and so on. Generally, fires and gas leaks can only be detected if the fire has already grown or a lot of smoke comes out of the building. Therefore, a monitoring system for detecting dangerous gases and fires in buildings based on the Internet of Things was created that can monitor the condition of the building through a website as well as send notifications to the Telegram application on smartphones. The detection system implemented uses a flame sensor as a fire detector, an MQ-2 gas sensor as a detector of hazardous gases (CO, CO2, and CH4), and NodeMCU as a module to transmit data. The system will work continuously in real time, if gas is detected that exceeds the threshold or a fire is detected, the system will send a notification to Telegram and the website will display the value and status of the sensor and a map of the area where the fire or gas leak occurred. The results of the detection system created to be able to provide solutions so that cases of fire and gas leaks can be handled early by detecting signs of fire or gas leaks and sending the information to users via the website and notifications.